VENTILATOR ASSOCIATED PNEUMONIA AMONG PATIENTS ON MECHANICAL VENTILATION AT TERTIARY CARE CENTRES: Ventilator Associated Pneumonia - Rafiq, Dr Muhammad Yasir; Ikram, Aamer; Afzal, Amna; Zaman, Gohar; Usman, Bushra; Ayyub, Muhammad (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the frequency of ventilator associated pneumonia (VAP) among patients on mechanicalventilation, and to identify the causative bacterial pathogens and antibiotic susceptibility pattern of isolatedmicroorganisms in intensive care units of tertiary care settings.Study Design: Descriptive cross sectional.Place and Duration of Study: This study was conducted at Microbiology Department, Armed Forces Institute ofPathology (AFIP), Rawalpindi, from Dec 2014 to Aug 2015.Material and Methods: A total of 176 patients on mechanical ventilation were included in the study; patientshaving respiratory tract infection before putting on ventilator were excluded. Endotracheal aspirate (ETA) andBronchoalveolar lavage (BAL) samples were collected aseptically from patients on mechanical ventilation on dayzero i.e. the day on which the patient was put on ventilator to rule out any previous respiratory tract infectionand then after 48 hours to observe the development of VAP. Samples were processed in the laboratory bystandard culture techniques, pathogens were identified and their antibiotic susceptibility was performed as perCLSI guidelines.Results: Out of 176 patients on mechanical ventilation, 59 (33.5%) developed VAP. Acinetobacter baumaniibeing the predominant pathogen isolated from 32 (54.2%) patients followed by MRSA 11 (18.6%), Klebsiellapneumoniae 9 (15.2%), Pseudomonas aeruginosa 5 (8.47%) and Stenotrophomonas maltophila from 2 (3.38%)patients.Conclusion: Frequency of VAP is quite high in our setup, identification of causative bacterial pathogens and theirantibiotic susceptibility pattern will not only help in providing effective treatment to the patients but will alsohelp in the formulation of antibiogram according to local resistance patterns for empirical therapy and to reducethe morbidity and mortality.